Impact of Histochemistry on Biomedical Research: Looking Through the Articles Published in a Long-established Histochemical Journal - Pellicciari, C. (Eur J Histochem, 2014)
Histochemistry provides the unique opportunity to detect single molecules in the very place where they exert their structural roles or functional activities: this makes it possible to correlate structural organization and function, and may be fruitfully exploited in countless biomedical research topics. Aiming to estimate the impact of histochemical articles in the biomedical field, the last few years citations of articles published in a long-established histochemical journal have been considered. This brief survey suggests that histochemical journals, especially the ones open to a large spectrum of research subjects, do represent an irreplaceable source of information not only for cell biologists, microscopists or anatomists, but also for biochemists, molecular biologists and biotechnologists.